CHALLENGES IN ACCESSING HEALTH CARE SERVICES IN AWO-OMAMMA, ORU EAST LOCAL GOVERNMENT AREA, IMO STATE, NIGERIA: A CROSS-SECTIONAL SURVEY RESEARCH DESIGN. - UROKO, FAVOUR; Morgan, Precious Rejoice (Student's Journal of Health Research Africa, 2024)
Background Challenges in access to healthcare facilities, especially in rural settings, have been a great concern to some scholars, and thus, a lot of studies have been carried out on this issue. This study focuses mainly on the challenges of access to the healthcare delivery system in Awo-mamma. The study critically looked at the challenges faced by the people of Awo-mamma in Imo State. Methods A simple random sampling method was used in selecting 200 respondents, and a convenience sampling method was adopted in selecting 3 interviewees for the in-depth interview, which represent both probability and non-probability sampling methods. Frequency and simple percentages were also used in the presentation, interpretation, and analysis of the data. The hypothesis was tested using Chi-Square (x2) inferential statistics, and it will help to bring out the relationship between different variables. Results The study discovered some of the challenges experienced by healthcare receivers, such as lack of money, distance, excessive wastage of time, unfair attitude of workers, etc., and those challenges experienced by healthcare givers, such as shortage of medical facilities, dilapidation of hospital buildings, ill-behaviour of patients towards medical staff, etc. These challenging factors make people seek medical attention/health care through other consequential means, such as patronizing the chemist shop, which lacks proper prescription, consulting the traditional cure, etc. Conclusion Sound health is a fundamental requirement for living a socially and economically productive life. Poor health inflicts great hardships on households, including debilitation, substantial monetary expenditures, loss of labor, and sometimes death. Recommendations Rural development policies should promote the creation of an enabling environment to enhance participation in modern healthcare delivery by organizing a sensitization program to create awareness about the importance of using modern healthcare facilities.